Developing food labelling strategies with the help of extremeness aversion - Ramona Weinrich; Achim Spiller (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2015)
Labelling is an important cue for consumers as it helps to quickly communicate information about a product or production process. However, the majority of labels on the market are binary, such as labels that indicate whether a product was produced using animal welfare friendly standards or not. Yet, there are many intermediate qualities that binary labels do not display. In the long run, if consumers are not able to identify if high quality attributes are contained in the product, due to a lack of information on the product label, then these attributes may disappear from the food market. In turn, this could lead to a market failure. A multi-level label can show different process standards of products explicitly. Nonetheless, before launching a multi-level labelling system, it should be tested if a multi-level labelling system can shift market shares in favour of the labelled products. Using a consumer study with 1538 German consumers (approximately representative for the German population regarding age, gender, income, education and regional distribution) the shares of product choices are calculated. Two comparisons of the shares of product choices will be made, one between no label and a binary label and the other between no label and a multi-level label. The results suggest that a multi-level labelling system achieves higher market shares, can improve animal welfare and can result in higher revenues or sales. The results deliver important information for policymakers in consumer policy and industry.
Keywords: 330; labelling; multi-level labelling; consumer research; animal welfare